Kemampuan Literasi Matematis Siswa SMP dalam Menyelesaikan Soal Setara AKM Ditinjau Berdasarkan Jenis Kelamin - Safitri Diah Pitaloka; Masriyah Masriyah (MATHEdunesa, 2026)
Mathematical literacy is an essential competency that enables students to formulate, apply, and interpret mathematics in real-life contexts. However, junior high school students’ mathematical literacy in solving Minimum Competency Assessment (MCA)-equivalent problems remains relatively low, especially in data and uncertainty content. In addition, studies examining mathematical literacy based on gender in MCA-equivalent contexts are still limited. Therefore, this study aims to describe junior high school students’ mathematical literacy abilities in solving MCA-equivalent problems based on gender differences. This study employed a qualitative descriptive approach involving one male student and one female student with equivalent mathematical abilities selected through purposive sampling. Data were collected through MCA-equivalent test items on data and uncertainty content and in-depth interviews. Data were analyzed through data reduction, data display, and conclusion drawing. The results showed differences in mathematical literacy characteristics between male and female students in formulating, employing, and interpreting processes. Female students tended to be more systematic in formulating problems and applying strategies, while male students showed greater confidence in interpreting results. However, both students still experienced difficulties in evaluating and justifying solutions, particularly on reasoning-level problems. The findings indicate that gender influences students’ mathematical literacy profiles in solving MCA-equivalent problems. Therefore, gender differences should be considered in designing mathematics learning and assessment activities.